2020
DOI: 10.3390/c6040081
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Graphene Oxide-Based Hybrids as Anodes for Lithium-Ion Batteries

Abstract: Presently, the negative electrodes of lithium-ion batteries (LIBs) are constituted by carbon-based materials, which exhibit a limited specific capacity 372 mAh g−1 associated with the cycle in the composition between C and LiC6. Therefore, many efforts are currently made towards the technological development of nanostructured graphene materials because of their extraordinary mechanical, electrical, and electrochemical properties. Recent progress on advanced hybrids based on graphene oxide (GO) and reduced grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 531 publications
(550 reference statements)
0
7
0
Order By: Relevance
“…The L‐GNS‐TiO 2 composite delivers reversible Li storage capacities of 173 and 330.6 mAh g −1 during the first cycle and after 450 cycles, respectively, at 0.15 A g −1 . The considerable increase in capacity can be attributed to an activation process of TiO 2 , which has been typically observed in metal sulfide or oxide‐based LIB anode materials 27,58‐61 . Moreover, the activation process of the electrode can be induced by the formation of a reversible polymeric gel‐like film upon the degradation of the activated electrolyte at a low potential through a so‐called “pseudo‐capacitance‐type behavior” due to the catalytic activity of the TiO 2 nanoparticles 23,26,59‐63 …”
Section: Resultsmentioning
confidence: 97%
“…The L‐GNS‐TiO 2 composite delivers reversible Li storage capacities of 173 and 330.6 mAh g −1 during the first cycle and after 450 cycles, respectively, at 0.15 A g −1 . The considerable increase in capacity can be attributed to an activation process of TiO 2 , which has been typically observed in metal sulfide or oxide‐based LIB anode materials 27,58‐61 . Moreover, the activation process of the electrode can be induced by the formation of a reversible polymeric gel‐like film upon the degradation of the activated electrolyte at a low potential through a so‐called “pseudo‐capacitance‐type behavior” due to the catalytic activity of the TiO 2 nanoparticles 23,26,59‐63 …”
Section: Resultsmentioning
confidence: 97%
“…Also, the aqueous 0.5 M Zn (CF 3 SO 3 ) 2 electrolyte supports better cycling stability by decreasing the water molecules surrounding Zn 2+ ions, thus improving charge transfer. [45][46][47] In Fig. 6, the series combination of the individual cell produces 12 V energy.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen-containing functional groups on GO's surface can act as an effective barrier against the permeation of electrolyte solvents, preventing their unwanted reactions with the electrode materials. This characteristic can significantly improve the cycling stability and safety of batteries, particularly in high-energy applications 56 . 57 Furthermore, the unique 2D structure of GO provides a large surface area for active material anchoring and facilitates efficient charge transfer during battery operation.…”
Section: Chipping Resistancementioning
confidence: 99%
“…Graphene oxide and its related compounds are emerging as promising binder materials for sodium-ion batteries and lithium–sulfur batteries. ,, Hao et al have suggested that free-standing rGO/CNT paper demonstrates capacitive charge storage, enhancing sodium ion storage and ensuring stable cyclability. This flexible rGO/CNT paper, proposed as a potential anode candidate for sodium-ion batteries, showcases an exceptional rate performance, maintaining a specific capacity of 101.4 mAh g –1 at a current rate density of 0.1 A g –1 , even under a demanding cycling rate of 5 A g –1 (refer to Figure ).…”
Section: Types Of Bindersmentioning
confidence: 99%